Pengaruh Brand Experience Terhadap Brand Loyalty Melalui Brand Love Pada Pengguna Laptop Merek Acer di Kota Cimahi - Aldy Wijaya; Hariyadi Triwahyu Putra (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to analyze the influence of brand experience on brand loyalty through brand love among users of Acer laptops in the city of Cimahi. The research instrument has undergone validity and reliability testing, classic assumption testing, simple regression testing, and multiple regression testing. The instrument was used to collect data from respondents who are at least 17 years old and have used Acer laptops, which are the objects evaluated in this study. The number of respondents involved in this research is 90 individuals. The data instrument analysis was conducted using the SPSS software version 27 and Sobel test. The findings of this study indicate that brand experience has a positive effect on brand love, brand experience has a positive effect on brand loyalty, and brand love also has a positive impact on brand loyalty. However, brand love does not significantly mediate the relationship between brand experience and brand loyalty. What sets this research apart from previous studies is its focus on the city of Cimahi and the use of the latest secondary data in 2023.